Welfare of invertebrates: a pilot study on a new land snail stunning technique - Paola Fossati; Federico M. Stefanini; Giuliano Ravasio; Umberto Coerezza (Scientific Reports, 2024)
Abstract The almost complete absence of regulations to protect invertebrates is a common condition in legal systems, including the European one, especially when it comes to invertebrates intended for human consumption. Thus, in the vast majority of cases, edible invertebrates do not receive even the most basic protection at slaughter. Despite recent research indicating that invertebrates are capable of feeling pain and stress, the humane step of stunning is not used on them. This is also the case for land snails, which are gastropod invertebrates whose consumption has now reached significant levels, already involving tonnes and that is expected to increase significantly as edible snail farming becomes more popular as a relatively low-cost, easy-to-perform, and sustainable alternative animal husbandry, thereby making land snails an increasingly economically important species. This paper presents and investigates a proposed stunning method based on the immersion of mollusks in CO2-supplemented and refrigerated water that could be used in the snail meat production chain to reduce the slaughter suffering of millions of these invertebrates. To this end, body condition descriptors (hemolymph parameters) in snails were determined before and after CO2 treatment in cold water, while generating useful data for defining a preliminary set of reference intervals for basal values.